Pharmaceutical property interpretation and biological property study on Ethionamide using quantum spectroscopic and computational tools. Issue 1 (11th December 2019) - Aarthi, R.; Ramalingam, S.; Periandy, S.
ABSTRACT: In this work, the molecular spectroscopic technique was used in a nonconventional way to predict the drug mechanism action of the drug compound, Ethionamide. The formatted molecular charge levels, due to the injection of substitutions in suitable positions, were measured. The molecular geometry distortion by the adoption of ligands in the ring system was noted at the nodal points of the core and the change of force constant of the heterogeneous intra-molecular assembly. The activity of the compositional parts of the molecule was purposively monitored from which the entire core and allied parts of the molecule were evaluated by the vibrational characteristics. The molecular reaction mechanism for saturating drug potential was observed from the chemical shift of core and substituted carbons. The fabricated charge transfer complex was identified and recognized from the base and ligand-binding structure. The major part of the exchange of electro-chemical quantized energy in non-bonding molecular orbitals for arranging biological activity in the compound was measured. The rule of five and Lipinski parameters to recognize the drug quality were checked and estimated.